Enhancing Students' Interest In Learning About Zakat in Islamic Religious Education Through Problem Based Learning Methods At Class VI Students of SDN 20 Sitiung - Andika, Darma (The Future of Education Journal, 2023)
This research is a research that aims to increase students' interest in learning in the subject of Islamic Religious Education in class VI of SD Negeri 20 Sitiung, Dharmasraya Regency. Dharmasraya Regency in 2023, to answer this question, the researchers used the Classroom Action Research (CAR) approach, then the authors explained as a theoretical basis regarding: understanding interest in learning, the Problem Based Learning method, Zakat. After the writer conducted research in the field, from the respondent's data there were 28 students. Then the author analyzed the data, it turns out that the 'hypothesis' that the author put forward is that if the Problem Based Learning method is carried out well on zakat material it can increase interest in learning Islamic Religious education because students' interest in learning in Islamic Religious education subjects in class is classified as low, namely 49%, this is based on the results observation before taking action. The results of the study after the action was taken, namely by applying the Problem Based Learning method, students' interest in learning increased. This increase can be seen from the results of observations in the first cycle and the second cycle. The first cycle with an average of 65%, while in the second cycle with an average of 86%. Based on this analysis, it can be concluded that the application of the Problem Based Learning method can increase the learning interest of class VI students at SD Negeri 20 Sitiung in Islamic education subjects